2013
DOI: 10.1111/1365-2664.12032
|View full text |Cite
|
Sign up to set email alerts
|

Effects of predator specialization, host plant and climate on biological control of aphids by natural enemies: a meta‐analysis

Abstract: Summary Aphids are among the most severe invertebrate pests of crops and cause high economic losses. The control of aphids by natural enemies is an essential ecosystem service with high relevance to management strategies applied in agricultural plant production and horticulture. However, the current knowledge on the effectiveness of specialist and generalist predators in aphid control with respect to host plants and climatic conditions has not yet been summarized in a meta‐analytical approach. We collected 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 50 publications
0
60
0
2
Order By: Relevance
“…The strong stabilizing effects of generalist predators on predator-prey cycles were already described in a theoretical study using a reactiondiffusion-advection modeling framework (Vitense et al, 2016). In addition, a meta-analysis of 60 predator-exclusion experiments with different specialized aphid predators showed similar results (Diehl et al, 2013). Assemblages that contained either only specialists or specialists and generalists had the greatest effect on the reduction of the aphid population compared to an assemblage of only generalists.…”
Section: Discussion Predator Specialization and Species Coexistencementioning
confidence: 58%
See 1 more Smart Citation
“…The strong stabilizing effects of generalist predators on predator-prey cycles were already described in a theoretical study using a reactiondiffusion-advection modeling framework (Vitense et al, 2016). In addition, a meta-analysis of 60 predator-exclusion experiments with different specialized aphid predators showed similar results (Diehl et al, 2013). Assemblages that contained either only specialists or specialists and generalists had the greatest effect on the reduction of the aphid population compared to an assemblage of only generalists.…”
Section: Discussion Predator Specialization and Species Coexistencementioning
confidence: 58%
“…In addition, species-specific traits, such as resource specialization, strongly affected prey biomass and diversity (Jiang and Morin, 2005;Filip et al, 2014) and induced shifts in trophic cascades (Steiner, 2001). Studies focusing on the combined effect of multiple predators with different resource utilization are unfortunately rare (Jiang and Morin, 2005;Diehl et al, 2013), but most likely better reflect natural communities and enable the direct observation of a major mediator of coexistence: resource partitioning (Chesson, 1991). Narwani and Mazumder (2010) showed that the overall consumption of specialist predators decreases at higher resource diversities, whereas generalist predators show an increase in consumption (Narwani and Mazumder, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The control of aphids, for example, by natural enemies is most promising in grass and herb crops, and is less suited for legume crops [108]. Perennial legume-grass mixtures strongly decrease the risk of annual summer weeds and also reduce annual winter weeds, especially if grown for three years [109].…”
Section: Pest and Weed Controlmentioning
confidence: 99%
“…Serviceproviding units* Predator density Menalled et al, 1999;Letourneau et al, 2009 Pest density Mols et al, 2007 Predator richness Duelli and Obrist, 2003 Species composition of pests and predators Bastian et al, 2013 Pest consumption rates Ingegno et al, 2013;Shrestha and Parajulee, 2013 Pest reduction Schmidt et al, 2003;Diehl et al, 2013 Ecosystem modification challenges in assessing ecosystem services arise from the need (i) to evaluate relationships between services and the kind of measures usually collected in ecological studies (e.g., species richness) and (ii) to account for the characteristics of ecological processes (e.g., dynamics, feedbacks, and uncertainties) in statistical models focusing on service provision. Final ecosystem services are often directly assessed, but such assessment does not provide information about contributing ecological processes or how management could be adapted to increase service provision.…”
Section: Category Measure Referencesmentioning
confidence: 99%
“…The assessment of biological control may therefore be improved if a small set of selected measures is included that covers aspects of service and disservice-providing units (e.g., pest consumption rates), ecosystem management (e.g., insecticide applications) and landscape modification (e.g., proportion of semi-natural habitats in the surrounding landscape; Table 2). Consideration of abiotic variables such as climate (Diehl et al, 2013) or soil characteristics (Birkhofer et al, 2008) will add to the explanatory power of this set of measures.…”
Section: Category Measure Referencesmentioning
confidence: 99%